Denitrification research based on green electron supply and cell metabolism regulation - LIU Chao; FAN Xinyun; ZHANG Xuemeng; CHEN Chuang; ZHU Mengru; CHEN Yinguang* (能源环境保护)
As a key link in the nitrogen cycle, microbial denitrification plays an important role in removing nitrate pollution from the water environment, realizing the return of nitrogen to the atmosphere, and maintaining nitrogen balance. Heterotrophic denitrification is the mainstream process of biological nitrogen removal at present. In the process of treating wastewater with a low carbon-to-nitrogen ratio, chemical carbon sources such as acetic acid are often added to obtain enough electron donors to achieve efficient nitrate removal. In recent years, researchers have focused on the development of novel electron donors such as photoelectrons, short-chain gaseous alkanes, and metabolism regulation methods to promote the utilization of electron donors. Firstly, the types of photosensitizers, the dominant functional microorganisms, the photosensitizer-microbe complex in the process of photoelectron-driven denitrification, and the application status of phototrophic denitrification are systematically reviewed. Then, the microbial metabolic pathway of denitrification using methane, propane, and other short-chain alkanes as carbon sources is described, the performance of kitchen waste and other organic wastes as carbon source is introduced, and the formation mechanism and utilization characteristics of microbial carbon sources are also analyzed. Finally, the mechanisms of promoting denitrification by improving electron utilization efficiency of microorganisms are discussed, in order to expand the understanding of efficient biological nitrogen removal mechanisms. The future exploration direction, such as the efficient supply of green electrons and the regulation of intracellular electron distribution, are proposed, aiming to provide reference for the development of biological denitrification technology.